Flies Without Borders : Lessons from Chennai on Improving India's Municipal Public Health Services - Das Gupta, Monica; Dasgupta, Rajib; Kugananthan, P.; Rao, Vijayendra; Somanathan, T.V.; Tewari, K.N. (World Bank, Washington, DC, 2017)
India's fast-growing cities face three key challenges in improving public health outcomes. The first is the persistence of weak links in the chain -- notably, slums badly underserved with basic civic services -- that can pose public health threats to all. Richer residents corner public resources, such as water and sanitation services, but their children's health indicators suggest they are deeply affected by contagion from the broader urban environment. The second challenge relates to devolution of services to elected bodies. Devolution works poorly for intangible and highly technical services, such as public health, where success is measured by the lack of (adverse) events. The third challenge is high fragmentation of services that directly affect health outcomes. In India, some cities have addressed these challenges more effectively than others have. This paper explores the management of municipal public health services in two major Indian metropolises with sharply contrasting health and sanitation indicators. The paper explains how Chennai mitigates these challenges through active service outreach to vulnerable populations, and a considered approach to devolution that distributes responsibilities appropriately between line agencies, technical personnel, and elected representatives. Services in Delhi are quite constrained. These policy lessons are pertinent to other Indian cities and beyond.